Nitrogen Retention and Productive Performance of Crossbred Native Chicken Due to Feeding Effect of Kayambang (Salvinia molesta) - Binti Ma'rifah; Umiyati Atmomarsono; Nyoman Suthama (Chemical Engineering Diponegoro University, 2013)
The present research was aimed to clarify the effect of feeding Salvinia molesta in crossbred native chicken on productive performance based on the ability of protein utilitation. The reseach was arranged in a completely randomized design with 4 treatments and 5 replications (5 birds each). The animals used in the present study were 100 birds of crossbred native chicken. The treatments given were as follows: T0 (diet without Salvinia molesta ), T1 (diet with 6% Salvinia molesta), T2 (diet with 12% Salvinia molesta), T3 (diet with 18% Salvinia molesta). Parameter observed namely feed consumption, nitrogen retention, muscle protein mass, and body weight gain. The data were analysed using anova, when the effect of the treatments was significant, then duncan’s multiple range test was applied. The results showed that the treatment of feeding Salvinia molesta indicated a sinificant effect (p<0.05) on nitrogen retention and productive performance. Feed consumption, nitrogen retention, muscle protein mass, and the body weight gain of T1, T2, and T3 were significantly higher (p<0.05) than those of control (t0), while among treatments T1, T2, and T3 were not different. Feeding Salvinia molesta up to the level of 18% can improve nitrogen retention and productive perfomance of crossbred native chicken.Doi: 10.12777/ijse.5.1.19-24[How to cite this article: Ma’rifah, U. Atmomarsono, N. Suthama. (2013). Nitrogen Retention and Productive Performance of Crossbred Native Chicken Due to Feeding Effect of Kayambang (Salvinia molesta), 5(1)2013.19-24. Doi: 10.12777/ijse.5.1.19-24 ]